Crystallization of bronze-like perovskite in potassium tantalum germanate glasses: Glass ceramic preparation and its optical properties - da Cunha, Cristiano Ramos; Marcondes, Lia Mara [UNESP]; Batista, Gislene; Gonçalves, Rogéria Rocha; Cassanjes, Fábia Castro; Poirier, Gael Yves (Elsevier, 2021)
Structural, optical and photoluminescent properties of Europium-doped potassium germanate glassy materials were investigated in terms of tantalum content and nanoscale crystallization of potassium tantalate K2Ta8O21. For such purpose, an Eu3+-doped germanate glass, Eu3+-doped tantalum germanate glass and Eu3+-doped tantalum germanate glass-ceramics were prepared and characterized by X-ray diffraction, Raman, UV–Vis–NIR and photoluminescence spectroscopies. Eu3+ emission properties were used as a sensitive probe to investigate its symmetry site into the host structure. The chemical microenvironment around Eu3+ ions have changed with tantalum concentration as well as bronze-like tantalum perovskite K2Ta8O21 phase crystallization into the glasses. The ions preferably occupy sites of higher symmetry and lower energy phonons, which attest the ions migration to the tantalum-rich crystalline environment. The correlation between the phonon side band (PSB) spectra and Raman vibrational modes, 5D0 → 7F2/5D0 → 7F1 ratio and experimental Eu3+ 5D0 lifetime support this assumption. The highest photoluminescence intrinsic quantum yield (QEuEu) is calculated for glass-ceramics heat-treated for 20 h by using Judd-Ofelt theory, indicating reduction of nonradiative decay processes due to the lower local phonon energy. The luminescence quenching for longer crystallization times demonstrates the importance of optimizing thermal treatment parameters to ensure proper distance between optically active ions. Accordingly, tantalum germanate glass-ceramics are promising for photonic devices as red laser, solid-state lighting and energy conversion applications, as well as for nonlinear optical applications considering the perovskite bronze-like crystallization.
Keywords: Europium; Glass; Glass-ceramics; Perovskite-like bronze; Tantalum